Brownfields - Element der Regionalen Wirtschaften - Kraft, Jiri (Brownfields - element gospodarki regionalnej, 2007)
The problem of the Brownfields has to be solved on their revitalization. Current methods have been trying to solve the problem ex post. It would be desirable to connect the Brownfields problem solution ex post with the solution ex ante. The solution to the problem can be left to the "invisible hand of the market" but it is true only in economically strong areas, where the demand for the invested space is higher than the supply and where it is impossible to find undeveloped land for construction. In economically weak areas it is necessary to motivate private investment by government expenditure directed to the Brownfields revitalization. It is right here where the government expenditure causes the maximum multiplication effect, which justifies its use. However, the government expenditures do not have to displace the private investment.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 68-78